Literary aesthetics of Klama lyrics: An exploration of allusion - Rebecca Gberki Angmor; William Dautey (Journal of African Languages and Literatures)
Folk songs have been a major part of ceremonies in most African societies of which the Krobo in Ghana are no exception. One striking type of folk music of the Krobo is Klama. Klama songs serve as a platform to instruct, entertain, educate as well as chastise wrong doers. In the belly of these songs are buried aesthetic devices which need to be unearthed. This study, therefore, sets out to investigate the use of allusion as an aesthetic device in Klama songs. It also aims at establishing and identifying the types of allusion in the songs. The study seeks to examine the effective use of Klama lyrics in communicating the history and beliefs of the Krobo. The study is anchored on the Infracultural framework of folklore analysis as the conceptual framework. The framework acknowledges that oral texts are deeply rooted in the culture and tradition of the performer and that the interpretation of an oral text must be situated within the cultural context. Data was collected through in-depth interviews, participant observation and information gathered from ethnographic records. The study reveals that biblical and historical allusions are important literary devices in Klama songs. It argues that allusion is heavily dwelt upon by Klama cantors to communicate the history and the beliefs of the Krobo ethnolinguistic group. This study documents Klama songs and contributes to the teaching of poetry and oral literature.  It also brings Klama songs to the lime light for scholarly attention.